2014
DOI: 10.1128/cmr.00124-13
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Human Cancers: a Long Road of Discovery of Molecular Paradigms

Abstract: SUMMARY About a fifth of all human cancers worldwide are caused by infectious agents. In 12% of cancers, seven different viruses have been causally linked to human oncogenesis: Epstein-Barr virus, hepatitis B virus, human papillomavirus, human T-cell lymphotropic virus, hepatitis C virus, Kaposi's sarcoma herpesvirus, and Merkel cell polyomavirus. Here, we review the many molecular mechanisms of oncogenesis that have been discovered over the decades of study of these viruses. We discuss how viruses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
144
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(145 citation statements)
references
References 180 publications
(218 reference statements)
0
144
0
1
Order By: Relevance
“…Viruses evade host immune responses and a variety of these strategies have been discussed elsewhere (9). In a similar manner, tumours overcome immune surveillance during their malignant progression, as has also been demonstrated in the case of EBV infection, which is present in about 90% of the world population.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Viruses evade host immune responses and a variety of these strategies have been discussed elsewhere (9). In a similar manner, tumours overcome immune surveillance during their malignant progression, as has also been demonstrated in the case of EBV infection, which is present in about 90% of the world population.…”
Section: Discussionmentioning
confidence: 86%
“…In their recent review, White et al indicated at least seven viruses that have been causally linked to human oncogenesis, stating that viruses can be involved in both tumour initiation and tumour progression (9). In general, DNA viruses affect cells by binding of the viral proteins to tumour-suppressor genes, and they also produce dsRNA-binding proteins that can act as suppressors of RNA silencing, thereby favouring tumour development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which EBV and HHV-8 may foster carcinogenesis are complex and not fully understood [31,32]. In both cases, common viral infections cause rare malignancies; this highlights the potential contribution of multifactorial nonviral factors to the development of infection-related cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EBV establishes long-term latent infections in B cells and may act just as an initial promoter of cellular transformation from which subsequent progression to cancer is independent [31,32]. The dominant EBV latency patterns observed in non-Hodgkin lymphoma tissue differ between pre- [33] and post-cART studies [34].…”
Section: Discussionmentioning
confidence: 99%